Effects of different forage to concentrate ratios on performance, plasma metabolites, and feeding behaviour of weaned dairy calves from 70 to 120 days of age. Issue 1 (1st January 2021) - Karami, Abbas; Alikhani, Masoud; Khorvash, Mohammad; Hashemzadeh, Farzad; Sadeghi-Sefidmazgi, Ali; Rafiee, Hassan; Ferraretto, Luiz F.
Abstract: Determining the best level of forage inclusion in diets for optimal performance of weaned calves will benefit the dairy industry greatly. This study evaluated the effect of feeding different forage to concentrate ratios on performance, behaviour, and metabolic responses of Holstein weaned calves. Forty-five Holstein female calves (70 d of age and 71.7 ± 4.4 kg body weight at trial initiation) were balanced for birth BW and randomly assigned to 1 of 3 treatments: (1) forage-to-concentrate ratio of 50:50, (2) forage-to-concentrate ratio of 35:65 and (3) forage-to-concentrate ratio of 20:80. Alfalfa hay was the sole dietary forage source. Calves were kept in individual pens until 120 d of age. Decreasing dietary forage concentration linearly increased dry matter and energy intake, and average daily gain. Body weight at d 95 and 120 linearly increased as alfalfa hay was replaced with concentrate. Ruminal pH at d 120 of age linearly decreased with greater inclusion of concentrate. Final heart girth, withers height and hip height linearly increased and final hip width tended to increase as concentrate was substituted for alfalfa hay. Plasma glucose concentration at d 95 of age linearly increased with greater concentrate levels, but the opposite was observed for β-hydroxybutyrate concentration. Increasing concentrate increased lying behaviour linearly, but decreased rumination behaviour. The results of this study indicated that feeding diets with a 20:80 forage to concentrate ratio enhanced feed intake, growth performance, and some skeletal growth parameters in the post-weaning period and increased lying behaviour and decreased rumination behaviour. HIGHLIGHTS: Determining the best level of forage inclusion in diets for optimal performance of weaned calves will benefit the dairy industry greatly. Decreasing dietary forage concentration linearly increased dry matter intake, body weight and withers height. Feeding diets with a 20:80 forage to concentrate ratio enhanced performance in the postweaning period of dairy calves.